France : Financial Sector Assessment Program-Technical Note-Issues in Insurance Supervision and Regulation. (IMF Staff Country Reports; Country Report ;, 2019)
This technical note focuses on issues in insurance supervision and regulation on France. France has a very high level of insurance penetration, particularly for life insurance. For each insurance company, a risk assessment is undertaken on at least an annual basis and is recorded in a supervisory review process tool. French insurance companies are significant users of the Volatility Adjustment (VA), with companies representing more than 90 percent of the technical provisions in the French insurance industry using the VA. The report discusses that French authorities should advocate to the relevant EU authorities to introduce a minimum number of independent members of the Administrative Management or Supervisory Boards, at least one-third. Autorite de Controle Prudentiel et de Resolution should review the intensity and frequency of on-site supervision and its relationship to off-site supervision. With several other meetings with insurance companies possible, some of these meetings may be close to be called as focused on-site inspections.